1995
DOI: 10.1016/s0022-5223(95)70090-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors obtained by a pathologic examination in completely resected non-small-cell lung cancer: An analysis in each pathologic stage

Abstract: We attempted to clarify what factors predominantly influence the survival of patients with non-small-cell lung cancer in each pathologic stage on the basis of information generally obtained by a pathologic examination of completely resected non-small-cell lung cancer. The subjects included 243 patients with stage I, 63 with stage II, and 108 with stage IIIA disease. Pathologic features used in the analysis were as follows: the greatest tumor size (< or = 3.0 cm versus > 3.0 cm), the histologic cell type (squam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
2
8

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(123 citation statements)
references
References 12 publications
(2 reference statements)
6
106
2
8
Order By: Relevance
“…In 2 large sĂ©ries, pleural involvement was found to be independently significant by multivariate and univariate analysis in stage I disease 5 and stage I and II disease. 6 Similar findings were found by univariate analysis in NI disease 7 and by univariate but not by multivariate analysis in stage I disease. 4 One study found poorer survival in patients with pi lĂ©sions compared with selected control subjects with pO lĂ©sions in squamous cell carcinoma.…”
Section: Bunker E T Al / Pleural Invasion In Lung Carcinomasupporting
confidence: 68%
See 1 more Smart Citation
“…In 2 large sĂ©ries, pleural involvement was found to be independently significant by multivariate and univariate analysis in stage I disease 5 and stage I and II disease. 6 Similar findings were found by univariate analysis in NI disease 7 and by univariate but not by multivariate analysis in stage I disease. 4 One study found poorer survival in patients with pi lĂ©sions compared with selected control subjects with pO lĂ©sions in squamous cell carcinoma.…”
Section: Bunker E T Al / Pleural Invasion In Lung Carcinomasupporting
confidence: 68%
“…Some studies confirm viscĂ©ral pleural invasion as an independent prognostic indicator. [4][5][6][7][8] The AJCC Cancer Staging Manual does not offer detailed advice on the diagnosis of viscĂ©ral pleural invasion. 9 Others, however, hĂąve proposed a useful staging classification, 10 with the following types: pO, no viscĂ©ral pleural involvement; pi, pĂ©nĂ©tration through the viscĂ©ral pleura elastic tissue but not to the surface of the viscĂ©ral pleura; p2, pĂ©nĂ©tration through to the surface of the viscĂ©ral pleura; and p3, involvement of pariĂ©tal pleura.…”
Section: Invasion Ofthe Viscéral Pleura Is An Important Component Oflmentioning
confidence: 99%
“…However, the impact of any non-nodal factor is less clear than in stage I disease. HOLMES [30] reported significant survival differences favouring squamous cell lung cancer in T1N1 and ICHINOSE et al [31] showed similar results in T1-2N1 disease. However, neither MARTINI et al [32] nor YANO et al [8] found any significant histological benefit favouring squamous cell lung cancer over nonsquamous cell lung cancer.…”
Section: Lung Cancer C-y Liu Et Almentioning
confidence: 90%
“…A previous study reported that nodal micrometastases were found in up to 36% of the resected lungs from the patients with peripheral NSCLC and the presence of metastases to the lymph nodes has been shown to immensely reduce the survival rates (26)(27)(28). Consequently, the development of a strategy to suppress lymphatic metastasis seems to be critical in the treatment of lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%